Long-term clinical outcomes of patients with chronic total coronary occlusion caused by intra-stent re-stenosis. (14th October 2021) - Gomez Monterrosas, O; Martin Yuste, V; Freixa, X; Brugaletta, S; Regueiro, A; Masotti, M; Sabate, M
Abstract: Objectives: In this study we aim 1) at identifying predictors of selecting percutaneous coronary intervention (PCI) to treat chronic total occlusion due to in-stent restenosis (CTO-ISR); and, 2) at comparing long-term clinical outcomes of patients treated with coronary artery by-pass graft (CABG), percutaneous coronary intervention (PCI) or optimal medical therapy (OMT). Methods: Between June 2010 and January 2014 a total of 1290 CTO were included in a prospective Registry. 86 of those patients presented with CTO-ISR. Clinical follow-up was obtained until April 2019. Major adverse cardiac events (MACE) rate was defined as the composite end-point of cardiac death, acute myocardial infarction or target lesion revascularization (TLR). Results: A total of 54 patients were treated with PCI (63%), 22 received OMT alone (25%) and the remaining 10 (12%) were treated with CABG. Patients treated with PCI were older and presented higher values of left ventricular ejection fraction than those of the other groups. From the anatomical point of view, calcification and ostial location were more frequently observed in the OMT group, whereas Syntax score was higher in the CABG arm. At multivariate analysis, age and Syntax score were the only independent predictors of selecting PCI. At long-term follow-up (mean 101 months), MACE rate was higher in the CABG arm mainly driven by a higher incidence of TLR. Conclusions: Percutaneous coronary intervention could be an effective and safe procedure to treat CTO-ISR. Larger prospective trials are required to confirm these clinical results. FUNDunding Acknowledgement: Type of funding sources: None.